Normative data for the Balance Tracking System modified Clinical Test of Sensory Integration and Balance protocol - Goble DJ (Dove Medical Press, 2019)
Daniel J Goble,1 Harshan Brar,1 Elise C Brown,2 Charles RC Marks,1 Harsimran S Baweja31Department of Human Movement Science, Oakland University, Rochester, MI, USA; 2Public and Environmental Wellness, Oakland University, Rochester, MI USA; 3School of Exercise and Nutritional Sciences, San Diego State University, San Diego, CA, USAPurpose: Force plate balance testing technology has traditionally been underutilized in clinical and research settings due to the high cost and lack of portability. A relatively new force plate called the Balance Tracking System (BTrackS) has been developed to overcome these barriers. BTrackS recently implemented the modified Clinical Test of Sensory Integration and Balance (mCTSIB) as a means of evaluating various sources of sensory information for postural sway control. The present study aimed to provide much needed normative data for the BTrackS mCTSIB protocol.Materials and methods: Data from 604 healthy adults (308 women; 296 men) between the ages of 18 and 29 years were collected according to the BTrackS mCTSIB protocol. The protocol consisted of four, 20-second static standing trials that manipulated relative contributions of the vision, proprioception and vestibular sensory systems through various eyes open/closed and foam/no foam conditions. Comparisons of men versus women and the impact of body size (ie body mass index) were determined so that relevant percentile rankings could be calculated.Results: Analysis of variance showed an interaction between sex and task condition on the BTrackS mCTSIB (p<0.001). This interaction indicated that women outperformed men on all conditions, but especially in the fourth trial where eyes were closed and standing was done on a compliant foam surface. Percentile rankings were calculated based on sex and BTrackS mCTSIB condition. No relationship was found between BTrackS mCTSIB results and body size.Conclusion: Normative data provided in this study are vital for establishing potential sensory feedback-based balance dysfunctions that may exist clinically or in laboratory settings. In addition, this data can aid in the tracking of changes over a rehabilitation period and/or the effectiveness of balance interventions.Keywords: postural sway, BTrackS, reference values, force plate, center of pressure